2013
DOI: 10.1088/0029-5515/53/4/043003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced deuterium retention in self-damaged tungsten exposed to high-flux plasmas at high surface temperatures

Abstract: We investigated the effect of surface temperature on deuterium retention in self-damaged tungsten exposed to high-flux deuterium plasmas. The retention saturates at a W 4+ fluence of about 3 × 10 17 m −2 and is strongly reduced for the present high surface temperatures of 800-1200 K as compared to previous experiments at 470-525 K. Combination of nuclear reaction analysis (NRA), thermal desorption spectroscopy and positron annihilation Doppler broadening (PADB) was used to investigate the reduction in deuteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 33 publications
6
46
0
Order By: Relevance
“…These blisters are similar to the ones described in Ref. [7], and probably originate from plastic deformation. On columnar coatings many more and larger blisters are observed (Fig.…”
Section: Blister Formationsupporting
confidence: 86%
See 1 more Smart Citation
“…These blisters are similar to the ones described in Ref. [7], and probably originate from plastic deformation. On columnar coatings many more and larger blisters are observed (Fig.…”
Section: Blister Formationsupporting
confidence: 86%
“…These nanostructures resemble the formations discussed in Ref. [7]. Xu et al characterized such structures and found that their appearance is dependent on the grain orientation [8].…”
Section: Nanostructure Formationsupporting
confidence: 69%
“…In addition, Edet decreases with increase in the number of D atoms trapped in a mono-vacancy [21,22]. This is one of the reasons for the broad desorption peak observed after the exposure at 473 K. Indeed, 't Hoen et al [23] performed positron annihilation Doppler broadening and D retention measurements for W specimen irradiated with 12.3MeV W ions and reported that clustering of vacancies took place at 650 K. They observed reduction in D retention with increase in the exposure temperature and explained this observation by the reduced amount of mono-vacancies and small vacancy clusters in combination with the strong depopulation with D due to thermal trapping and detrapping [23]. In any case, an improvement of modelling such as TMAP is necessary to analyse the desorption spectra acquired under the conditions where annealing of defects is significant.…”
Section: Thermal Stability Of Defects Formed By Ion Irradiationmentioning
confidence: 99%
“…The program includes trapping of deuterium and recombination to molecules at the surface. Following our previous results [9], we assume three different trap sites for deuterium in tungsten with trap densities of 2 Â 10 À1 , 4:5 Â 10 À1 , and 6:5 Â 10 À1 at. % for trapping energies of 1.2, 1.4, and 1.85 eV, respectively.…”
Section: Cannot Explain Thismentioning
confidence: 99%
“…The surface cleanliness was checked by x-ray photoelectron spectroscopy. Since the targets were PRL 111, 225001 (2013) P H Y S I C A L R E V I E W L E T T E R S week ending 27 NOVEMBER 2013 stored under ambient conditions, they were covered with nanometer-thick native layers of oxygen and carbon [3,9]. During plasma exposure, most of these layers are removed within the first few seconds, although the presence of in particular some oxygen cannot be excluded [10].…”
mentioning
confidence: 99%